2008
DOI: 10.1091/mbc.e08-02-0206
|View full text |Cite
|
Sign up to set email alerts
|

Head–Head and Head–Tail Interaction: A General Mechanism for Switching Off Myosin II Activity in Cells

Abstract: Intramolecular interaction between myosin heads, blocking key sites involved in actin-binding and ATPase activity, appears to be a critical mechanism for switching off vertebrate smooth-muscle myosin molecules, leading to relaxation. We have tested the hypothesis that this interaction is a general mechanism for switching off myosin II-based motile activity in both muscle and nonmuscle cells. Electron microscopic images of negatively stained myosin II molecules were analyzed by single particle image processing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
230
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(255 citation statements)
references
References 54 publications
18
230
1
Order By: Relevance
“…Interestingly, the authors reported that cardiac RLC phosphorylation does not lead to a disordered structure and an ordered RLC-thick filam e n t ba c kb o n e i n t e r a c t i o n i s m a i n t a i n e d po s tphosphorylation even in the calcium-activated systolic state (Kampourakis and Irving 2015). This evidence challenges the previous studies that (1) implicated Bweakening/breakingm echanism by which RLC phosphorylation controls myosin head conformation by disrupting a compact OFF conformation of myosin (Jung et al 2008) or (2) maintained that RLC phosphorylation produces an order-to-disorder transition in skeletal muscle thick filaments (Levine et al 1995;Stewart et al 2010). The study also suggested a rather global change in RLC environment associated with changes in tertiary structure/intermolecular interactions, which argues against a previously reported unchanged conformation postphosphorylation in scallop catch muscle myosin (Kampourakis and Irving 2015;Kumar et al 2011).…”
Section: Structural Effects Associated With Myosin Rlc Pseudo/phosphocontrasting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, the authors reported that cardiac RLC phosphorylation does not lead to a disordered structure and an ordered RLC-thick filam e n t ba c kb o n e i n t e r a c t i o n i s m a i n t a i n e d po s tphosphorylation even in the calcium-activated systolic state (Kampourakis and Irving 2015). This evidence challenges the previous studies that (1) implicated Bweakening/breakingm echanism by which RLC phosphorylation controls myosin head conformation by disrupting a compact OFF conformation of myosin (Jung et al 2008) or (2) maintained that RLC phosphorylation produces an order-to-disorder transition in skeletal muscle thick filaments (Levine et al 1995;Stewart et al 2010). The study also suggested a rather global change in RLC environment associated with changes in tertiary structure/intermolecular interactions, which argues against a previously reported unchanged conformation postphosphorylation in scallop catch muscle myosin (Kampourakis and Irving 2015;Kumar et al 2011).…”
Section: Structural Effects Associated With Myosin Rlc Pseudo/phosphocontrasting
confidence: 54%
“…The predicted structures were then modeled using the PyMOL (www.pymol.org) molecular visualization system to allow determination of the C-α distances (Å) between neighboring amino acid residues. From Yuan et al (2015) of isolated myosins and thick filaments suggested a conserved molecular mechanism in which RLC phosphorylation activates or potentiates contractility by disrupting a compact 'OFF' conformation of myosin in which the myosin heads are folded back on the myosin tail (Jung et al 2008;Wendt et al 2001;Woodhead et al 2005). Using bifunctional rhodamine probes on the cardiac RLC, Kampourakis et al have reported that phosphorylation enhances active force and its Ca 2+ -sensitivity and alters thick filament structure, with the myosin head domains becoming more perpendicular to the filament axis (Fig.…”
Section: Structural Effects Associated With Myosin Rlc Pseudo/phosphomentioning
confidence: 99%
“…However, it is worth noting that earlier work using a 93 amino acid peptide from the coiled-coil forming region of scallop muscle myosin-2 also gave rise to an APCC structure (53), but this was known to form a parallel coiled-coil in the context of the full-length molecule (54). At present, the resolution of our negatively stained EMs, obtained using recombinant M10HMM with the leucine zipper sequence after amino acid 936, does not allow us to discern the tail structure directly.…”
Section: Discussionmentioning
confidence: 99%
“…Purified NanR, the NanR/ ligand complex, and the NanR/DNA complex were diluted to a final concentration of 300 nM with 50 mM Tris·HCl (pH 7.0) and 300 mM NaCl. Five microliters of the sample solution were applied to a carbon-coated grid, which had been glow-discharged (Harrick Plasma) for 3 min in air, and the grid was negatively stained immediately by using 1% uranyl acetate (44). The grids were examined by using a Technai G2 Spirit Twin transmission electron microscope (FEI) operated at 120 kV, and the images were recorded on a 4K × 4K Ultrascan 895 CCD (Gatan) at a magnification of 0.36 nm/pixel.…”
Section: Methodsmentioning
confidence: 99%